Pengaruh Beban Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan pada Wisata Kampung Turis Karawang - Siti Elisah Widiah Astuti; Budi Rismayadi; Wike Pertiwi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the influence of workload and work discipline on employee performance at the Karawang Tourist Village Tourism. The research method used is a quantitative approach with a saturated sampling technique (Total Sampling), with a population of 56 employees. Data was collected using a questionnaire and analyzed using multiple linear regression. The research results show that workload does not have a significant influence on employee performance, with a regression coefficient value of -0.043 and a significance value of 0.741. Work discipline also has a significant effect on performance, with a regression coefficient of 0.242 and a significance value of 0.001. Simultaneously, workload and work discipline are able to explain 18.9% of the variation in employee performance. These findings emphasize the importance of measurable workload management and implementing a consistent culture of discipline to improve employee performance. This research provides recommendations for management to balance workload, strengthen a culture of work discipline, and pay attention to the balance between work and employees' personal lives in order to achieve optimal performance.